A comparison of magnetic resonance venography findings and venous occlusion plethysmography variables in postthrombotic syndrome. (August 2017) - Blomgren, Lena; Engström, Jan; Rosfors, Stefan
Objective: The relation between venous morphology and venous function in postthrombotic syndrome is poorly understood. The aim of this study was to compare obstruction and collateralization as seen with magnetic resonance venography with variables of venous occlusion plethysmography in patients with postthrombotic syndrome. Methods: Medical records, magnetic resonance venography and venous occlusion plethysmography data were analyzed in 28 patients (33 legs). Magnetic resonance venography images were scored for degree of obstruction and collateralization in segments of pelvic and abdominal veins and correlated to venous occlusion plethysmography data. Results: Obstruction of the inferior vena cava correlated with an overall increase of collaterals ( p < 0.001). The summary scores of collaterals or obstructions did not correlate with venous occlusion plethysmography variables. Relative expelled volume at 4 s correlated inversely with obstruction of the inferior vena cava ( p = 0.045) and vertebral collateralization ( p = 0.033). Conclusions: Modest correlations were found between magnetic resonance venography scores and venous occlusion plethysmography variables. Prospective studies with refined scoring and magnetic resonance venography techniques may increase our knowledge further.